Voluntary Affirmative Action. Does it Work? - Burt, Sandra (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
The study focuses on affirmative action programs for women employees and seeks to measure attitudes offirms and their participation in such programs.